First observations of two talitrid crustaceans (Amphipoda: Talitridae) from Gokceada island (NE Aegean Sea) - CAMUR-ELIPEK, B.; ASLAN-CIHANGIR, H. (Mediterranean Marine Science, 2006)
The present paper reports the occurrence of Talitrus saltator (Montagu, 1808) and Orchestia gammarellus (Pallas, 1766) which are the first records from Gokceada (Imbroz) Island (NE Aegean Sea). It should be noted that, T. saltator is a new record for the Aegean Sea coast of Turkey.